2023
DOI: 10.7150/thno.80091
|View full text |Cite
|
Sign up to set email alerts
|

Strategies targeting PD-L1 expression and associated opportunities for cancer combination therapy

Abstract: Immunotherapy has achieved great success recently and opened a new avenue for anti-tumor treatment. Programmed cell death 1/programmed cell death ligand 1 (PD-1/PD-L1) are typical immune checkpoints that transmit coinhibitory signals, muting the host immunity. Monoclonal antibodies that block PD-1/PD-L1 axis have benefited many patients with different tumor diseases. However, the objective response rate is still unsatisfactory. In this review, we summarize three strategies targeting PD-L1 based on different fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 184 publications
0
19
0
Order By: Relevance
“…The downregulation of PD-L1 has been widely recognized as one of the most effective approaches to alleviate T-cell exhaustion. , Therefore, the remaining portion of the tumor tissue from each group was subjected to immunofluorescence analysis to examine the presence of different T lymphocyte populations infiltrating tumors (Figure B). Due to the strong modulation of PD-L1 by anti-PD-L1 and MHI-TMX@ALB, either treatment individually or in combination with PDT, there was a notable enhancement in the infiltration of CD3 + , CD4 + , and CD8 + T-cells into MB49 tumors when treated with MHI-TMX@ALB or anti-PD-L1 monoclonal antibody (Figure B).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The downregulation of PD-L1 has been widely recognized as one of the most effective approaches to alleviate T-cell exhaustion. , Therefore, the remaining portion of the tumor tissue from each group was subjected to immunofluorescence analysis to examine the presence of different T lymphocyte populations infiltrating tumors (Figure B). Due to the strong modulation of PD-L1 by anti-PD-L1 and MHI-TMX@ALB, either treatment individually or in combination with PDT, there was a notable enhancement in the infiltration of CD3 + , CD4 + , and CD8 + T-cells into MB49 tumors when treated with MHI-TMX@ALB or anti-PD-L1 monoclonal antibody (Figure B).…”
Section: Resultsmentioning
confidence: 99%
“…46,52 Thus, the acquired immune resistance after PDT seriously limited its further clinical usage. 18,19 To solve this problem, MHI-TMX@ALB nanoparticles were established in this study (Scheme 1). Unlike some traditional PDT nanosystem encapsulating some typical PDT drugs like verteporfin, IR780, Ce6, SORgenTAM, etc., all-in-one MHI-TMX@ALB nanoparticles had incomparable merits like tumor targeting, self-PD-L1/TGF-β combined depression capacity, and self-hypoxia reversion function, which almost totally reversed acquired immune resistance after PDT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Tumor cells exploit this molecular mechanism to escape immune surveillance by overexpressing immune checkpoint molecules and promoting tumor growth. In addition, anti-PD-1/PD-L1 immunotherapy characterized by accurate effect, good tolerance, wide indications, and high specificity has shown high efficacy in a wide variety of cancers, such as nonsmall cell lung cancer (NSCLC), colorectal cancer, melanoma, and so on. However, not all patients respond to the ICI-based treatment, and only 10–30% of patients have just benefited from the therapeutic schedule as a whole. , Researchers indicated that the clinicopathologic features and clinical outcome of patients were closely related to the expression level of PD-L1. Accordingly, it is essential to accurately select the potential beneficiaries of anti-PD-1/PD-L1 immunotherapy.…”
Section: Introductionmentioning
confidence: 99%